A theory of shortage in socialist economies based on the `soft budget constraint' - Qian, Yingyi (American Economic Review, 1994)
This paper attributes shortages of goods in socialist economies to the soft financial constraints that firms in such economies face. A 'soft budget constraint' problem arises when the state bank is unable to make a credible commitment not to refinance bad projects once some investment costs are sunk. In such a situation, if a consumer good is also demanded by firms as an input and the seller cannot separate firms from households, the high market-clearing price would lead to welfare losses because too many bad projects would start and crowd out household consumption. Copyright 1994 by American Economic Association.